Analysis of A 5 Kw Solar - PV System with Model Predictive Controlled: Boost Converter for An Office Suite - Big-Alabo, Ameze (European Journal of Applied Sciences, 2024)
This study considers the design analysis and simulation of a 5 kW Solar –Photovoltaic (PV) system with Model Predictive Controlled (MPC) – boost converter for a typical office suite. A departmental office at the faculty of Engineering, University of Port Harcourt is used as a case study. Measurement readings of the power consumed by the office is conducted to ascertain the average load power of the building. The maximum power recorded is 3.52 kW. Therefore, a 5 by 5 series-parallel solar PV array is designed to yield a total output power of 5 kW to cover for possible additional loads in the system. The MPC – boost converter with parameters L = 1 mH and C = 600 mF and R = 0.01 Ω was designed to help maintain stable voltage whenever there is a drop in solar irradiance or variation in the consumer load. The focus of this study is on the variation in consumer load while the solar irradiation is maintained at maximum value. Thus, the designed PI controller is more of an integral action with values of Kp = 0.012, and Ki = 10. The MPC – boost converter and PI controller was able to maintain stable total voltage of 132 V despite the load variation due to switching on and off of consumer load.